Hydrogen isotopic differences between C3 and C4 land plant lipids: consequences of compartmentation in C4 photosynthetic chemistry and C3 photorespiration. (3rd October 2016) - Zhou, Youping; Grice, Kliti; Stuart‐Williams, Hilary; Hocart, Charles H.; Gessler, Arthur; Farquhar, Graham D.
Abstract: The 2 H/ 1 H ratio of carbon‐bound H in biolipids holds potential for probing plant lipid biosynthesis and metabolism. The biochemical mechanism underlying the isotopic differences between lipids from C3 and C4 plants is still poorly understood. GC‐pyrolysis‐IRMS (gas chromatography‐pyrolysis‐isotope ratio mass spectrometry) measurement of the 2 H/ 1 H ratio of leaf lipids from controlled and field grown plants indicates that the biochemical isotopic fractionation (ε 2 Hlipid_biochem ) differed between C3 and C4 plants in a pathway‐dependent manner: ε 2 HC4 > ε 2 HC3 for the acetogenic pathway, ε 2 HC4 < ε 2 HC3 for the mevalonic acid pathway and the 1‐deoxy‐D‐xylulose 5‐phosphate pathway across all species examined. It is proposed that compartmentation of photosynthetic CO2 fixation into C4 mesophyll (M) and bundle sheath (BS) cells and suppression of photorespiration in C4 M and BS cells both result in C4 M chloroplastic pyruvate – the precursor for acetogenic pathway – being more depleted in 2 H relative to pyruvate in C3 cells. In addition, compartmentation in C4 plants also results in (i) the transferable H of NADPH being enriched in 2 H in C4 M chloroplasts compared with that in C3 chloroplasts for the 1‐deoxy‐D‐xylulose 5‐phosphate pathway pathway and (ii) pyruvate relatively 2 H‐enriched being used for the mevalonic acid pathway in the cytosol of BS cells in comparison with that in C3 cells. Abstract : Analysed the 2 H/ 1 H ratio of carbon‐bound hydrogens of controlled and field grown C3 and C4 plant leaf lipids. C3 versus C4 differences in lipid‐over‐leaf‐water 2 H depletion are lipid pathway‐dependent. Compartmentation and photorespiration identified as the biochemical bases for such differences.